Competitiveness Strategy for Silk Craftsmen in Wajo Regency - Andi Asriadi AP Andi Asriadi AP (Pustaka Digital Indonesia, 2022)
This research was motivated by the increasingly competitive conditions of the silk industry. Knowledge of the silk industry players as a cottage industry about the importance of power strategies and improving the quality of the products produced needs to be improved considering that small businesses are the backbone of a country's economy. By fostering the silk industry in the Department of Industry, Trade, Cooperatives and SMEs of Wajo Regency, it is mandatory for the silk industry players to be able to compete by developing a competitive strategy to be able to create products with low production costs, superior , unique, different and focused on creating a market for businesses run by silk industry players. The results showed that the competitive strategy of the silk industry was quite good when viewed from 3 strategic aspects, namely cost leadership (low costs including production costs, tools and raw materials), differentiation (creating different and unique products), and focus (target buyers, segments). products and marketing locations). In terms of differentiation, the Wajo Regency Industry, Cooperatives and SMEs are superior in this strategy. This can be seen from the form of coaching, training, technical guidance or entrepreneurship workshops attended by silk industry players which have had a positive effect on several silk industry players in Wajo Regency.